Comparison of Giving Peppermint Aromatherapy and Lemon Aromatherapy Against Vomiting Nausea in Pregnant Women with Hyperemesis Gravidarum Level I - Yulia Herliani; Herni Kurnia; Ismah Khaerunisa (JURNAL KEBIDANAN, 2023)
According to WHO, symptoms of nausea and vomiting are experienced by around 70% of pregnant women in the first trimester. Management for nausea and vomiting can be pharmacological or non-pharmacological. One of the non-pharmacological treatments is peppermint aromatherapy and lemon aromatherapy which can overcome or eliminate nausea and vomiting. The purpose of this study was to compare the administration of peppermint aromatherapy and lemon aromatherapy to nausea and vomiting in pregnant women with Hyperemesis Gravidarum Level I in the Work Area of the Cigalontang Health Center in 2021. The research method is Quasy Experiment with  two group pretest-posttest design. The samples in this study was 32 respondents with total sampling technique. Giving aromatherapy, both peppermint aromatherapy and lemon aromatherapy, is done by giving two drops of aromatherapy that the researcher bought with the brand "N" on the tissue that the researcher bought with the brand "T" then the tissue is stored in the chest, then inhale for 10 minutes. Giving aromatherapy is given 2 times at 06.00 WIB and 18.00 WIB. Giving is done 6 days in a row. The statistical test uses Paired-Sample T-Test to determine the effect of the intervention, and uses Independent T-Test to compare the effect of the intervention. The results of the analysis obtained a p value of 0.000 which means that there is a difference in the scale of nausea and vomiting in pregnant women with level I hyperemesis gravidarum in the Work Area of the Cigalontang Health Center in 2021 which was given intervention by giving peppermint and lemon aromatherapy.The conclusion in this study is that peppermint aromatherapy is more effective than lemon aromatherapy against nausea and vomiting in pregnant women with Hyperemesis Gravidarum Level I in the Work Area of the Cigalontang Health Center in 2021.